2013
DOI: 10.1166/jnn.2013.7734
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Scale Surface Morphology Evolution of Cu/Ti Thin Films

Abstract: This paper discusses solid-phase reaction, agglomeration and dendritic growth of Cu/Ti/Si thin films with different sublayer thickness, 70 nm Cu/20 nm Ti/Si and 20 nm Cu/70 nm Ti/Si, annealed using rapid thermal annealing (RTA) method at the temperature from 500 degrees C to 800 degrees C. The crystal structure is examined using XRD, and the surface morphology is measured by SEM and AFM. The sheet resistance is measured using four-point probe method. The dendritic patterns can be obtained in both thin films at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…It is shown that the surface roughness is influenced by thickness of Ti layer and Cu layer in the double-layer heterostructure. The simulated surface morphology and roughness shows a good agreement with micrographs and measured data of experiments [1].…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…It is shown that the surface roughness is influenced by thickness of Ti layer and Cu layer in the double-layer heterostructure. The simulated surface morphology and roughness shows a good agreement with micrographs and measured data of experiments [1].…”
Section: Introductionsupporting
confidence: 79%
“…The surface morphology of nano-thin films has great influence on the physical/chemical properties of the thin film system [1][2][3]. However, the mechanism controlling the surface morphology/roughness of the heterostructure films is still not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Fan et al [29], Sun et al [32], and Umar and Oyama [33], Journal of Nanomaterials Heat absorption of a system can be given as = Δ , where is specific heat capacity, is the mass related to the thickness, and Δ is the change of temperature. In the 70 nmCu/20 nmTi/Si film system reported in our previous research [27], the thickness of Si substrate (0.4 mm) is bigger than the film thickness for several orders of magnitude, so the substrate will play a major role in the endothermic process. For the same absorption heat, when the substrate thickness increases, the change of temperature becomes smaller.…”
Section: Resultsmentioning
confidence: 89%
“…In our previous research [27], two Cu/Ti thin film systems (70 nmCu/20 nmTi/0.4 mmSi ⟨100⟩ and 20 nmCu/ 70 nmTi/0.6 mmSi ⟨100⟩) were deposited. The surface morphology evolution of the two thin films was different.…”
Section: Introductionmentioning
confidence: 99%